Analisis Persepsi Guru PPKn terhadap Pemanfaatan MagicSchool.ai dalam Pemberian Feedback Asesmen Formatif - Deva Deswitama; Yan Amal Abdilah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes to education, particularly in assessment practices that were previously manual and time-consuming. One emerging platform is MagicSchool.ai, which offers various features to assist teachers in designing assessment rubrics, generating questions, and providing adaptive and constructive feedback. This study aims to analyze the effectiveness and challenges of using MagicSchool.ai in rubric development and feedback delivery, as well as to examine the integration of AI with teachers’ roles in formative assessment. The research employed a qualitative descriptive approach involving 24 PPKn teachers from MGMP Kendal Regency who completed open-ended online questionnaires via Google Forms. Data were analyzed thematically to identify key themes from teachers’ perceptions. The findings reveal that MagicSchool.ai is considered effective in providing feedback that is consistent with learning objectives, clear, fast, actionable, and sustainable, thereby fostering students’ critical and reflective thinking. However, challenges such as limited device access, language complexity, and contextual detail remain. The study concludes that MagicSchool.ai functions as a collaborative partner for teachers rather than a replacement, with its effectiveness depending on integration with teachers’ reflective roles. Looking ahead, AI-based assessment has the potential to enhance efficiency, objectivity, and learning quality, provided that it is supported by adequate infrastructure and teachers’ digital literacy.